The Arabs in America, 1492-1977 : a chronology & fact book - Mehdi, Beverlee Turner, 1930- (Dobbs Ferry, N.Y. : Oceana Publications, 1978)
A history of Arabs in the United States with illustrative documents, appendices, and bibliography.
Includes index.
Bibliography: p. 143-146.
Keywords: Arab Americans -- History; Arab Americans -- History